Development of Teaching Materials related Magnetic Field Based on the Google Sites Assisted Learning Cycle Model - Yusuf, Dwi Sukmawati A.; Rahman, Mardia Hi; Saprudin; Hamid, Fatma (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2023)
The development of computer technology provides an opportunity for educators to innovate in the development of digital teaching materials. This development research aims to: 1) develop magnetic field teaching materials based on the Google sites assisted learning cycle model for grade XII students of Madrasah Aliyah, 2) investigate the feasibility of magnetic field teaching materials developed, 3) investigate improvements in student learning outcomes by using teaching materials developed, 4) investigating student responses to the use of teaching materials developed in physics learning. This development research refers to the 5 stages of the ADDIE development design which includes the analyze, design, develop, implementation, and evaluation stages. The validation of teaching material products involves material experts, media experts and language experts, each of which consists of 3 validators. The teaching material product was implemented by involving 20 students grade XII at one of the Madrasah Aliyah in the City of Tidore Kepulauan. Data collection techniques used in this study were validation sheets, test instruments in the form of multiple choice questions and questionnaires. The results showed that teaching material products based on the Google sites assisted learning cycle model were declared feasible for use in learning. Student learning outcomes have increased after participating in learning. Students also gave very good responses to the use of teaching materials developed in this study.